Revisited clinical implication of 99mTc-Sestamibi scan for staging Multiple Myeloma as an affordable alternative modality: A Case report - Naznin, Afroza; Sarker, Azmal K; Rahman, Hosne Ara; Sharmin, Samira; Hossain, Jamiul (Bangladesh Journal of Nuclear Medicine, 2021)
Background: Staging of multiple myeloma (MM) requires quantification of lesions and serum biomarkers. Sestamibi (MIBI) scan can detect medullary and extra-medullary lesions whereas pathological fracture of MM when associated with osteoblastic activity which can be imaged by methyl diphosphonate (MDP). Patients and methods: This case report is of a biopsy proven case of MM with serum biomarkers inconclusive for staging. With evidence of multiple pathological rib fractures on conventional radiography, the patient was sent for MDP scan as she was unable to afford any other modality for whole body survey. A complimentary MIBI scan was therefore done. Results: MDP scan revealed multiple osteoblastic lesions in spine and ribs. The MIBI scan was conclusive for stage II active disease. Conclusions: MIBI scan added to diagnostic information and aided an inexpensive staging. MIBI scan can be an affordable work-up tool for MM. Bangladesh J. Nuclear Med. 22(2): 150-154, Jul 2019